Melatonin administered during the fetal stage affects circadian clock in the suprachiasmatic nucleus but not in the liver - Houdek, Pavel; Polidarová, Lenka; Nováková, Marta; Matějů, Kristýna; Kubík, Štěpán; Sumová, Alena (Developmental neurobiology, 2015)
The mammalian circadian system develops gradually during ontogenesis, and after birth, the system is already set to a phase of the mothers. The role of maternal melatonin in the entrainment of fetal circadian clocks has been suggested, but direct evidence is lacking. In our study, intact or pinealectomized pregnant rats were exposed to constant light (LL) throughout pregnancy to suppress the endogenous melatonin and behavioral rhythms. During the last 5 days of gestation, the rats were injected with melatonin or vehicle or were left untreated. After delivery, daily expression profiles of c-fos and Avp in the suprachiasmatic nuclei (SCN), and Per1, Per2, Rev-erbα, and Bmal1 in the liver were measured in 1-day-old pups. Due to the LL exposure, no gene expression rhythms were detected in the SCN of untreated pregnant rats or in the SCN and liver of the pups. The administration of melatonin to pregnant rats entrained the pups' gene expression profiles in the SCN, but not in the liver. Melatonin did not affect the maternal behavior during pregnancy. Vehicle injections also synchronized the gene expression in the SCN but not in the liver. Melatonin and vehicle entrained the gene expression profiles to different phases, demonstrating that the effect of melatonin was apparently not due to the treatment procedure per se. The data demonstrate that in pregnant rats with suppressed endogenous melatonin levels, pharmacological doses of melatonin affect the fetal clock in the SCN but not in the liver.
Keywords: cirkadiánní proteiny Period; Circadian Clocks; suprachiasmatic nuclei; circadian system; Animals, Newborn; Rats, Wistar; ARNTL Transcription Factors; vývojová regulace genové exprese; transkripční faktory ARNTL; Corticosterone; Gene Expression Regulation, Developmental; clock gene; Arginine Vasopressin; Suprachiasmatic Nucleus; potkani Wistar; melatonin; mateřské chování; arginin vasopresin; novorozená zvířata; Maternal Behavior; Melatonin; světlo; krysa rodu Rattus; Animals; kortikosteron; ženské pohlaví; játra; nucleus suprachiasmaticus; Period Circadian Proteins; zvířata; pohybová aktivita; Rats; ontogenesis; Motor Activity; protoonkogenní proteiny c-fos; jaderné receptory - podrodina 1, skupina D, člen 1; Liver; Light; Female; Proto-Oncogene Proteins c-fos; cirkadiánní hodiny; Nuclear Receptor Subfamily 1, Group D, Member 1